MARCH5 RNA promotes autophagy, migration, and invasion of ovarian cancer cells. Issue 2 (1st February 2017) - Hu, Jianguo; Meng, Ying; Zhang, Zhanqin; Yan, Qiuting; Jiang, Xingwei; Lv, Zilan; Hu, Lina
ABSTRACT: MARCH5 is a crucial regulator of mitochondrial fission. However, the expression and function of MARCH5 in ovarian cancer have not been determined. This study investigated the expression and function of MARCH5 in ovarian cancer with respect to its potential role in the tumorigenesis of the disease as well as its usefulness as an early diagnostic marker. We found that the expression of MARCH5 was substantially upregulated in ovarian cancer tissue in comparison with the normal control. Silencing MARCH5 in SKOV3 cells decreased TGFB1-induced cell macroautophagy/autophagy, migration, and invasion in vitro and in vivo, whereas the ectopic expression of MARCH5 in A2780 cells had the opposite effect. Mechanistic investigations revealed that MARCH5 RNA may function as a competing endogenous RNA (ceRNA) to regulate the expression of SMAD2 and ATG5 by competing for MIR30A . Knocking down SMAD2 or ATG5 can block the effect of MARCH5 in A2780 cells. Also, silencing the expression of MARCH5 in SKOV3 cells can inhibit the TGFB1-SMAD2/3 pathway. In contrast, the ectopic expression of MARCH5 in A2780 cells can activate the TGFB1-SMAD2/3 pathway. In turn, the TGFB1-SMAD2/3 pathway can regulate MARCH5 and ATG5 through MIR30A . Overall, the results of this study identified MARCH5 as a candidate oncogene in ovarian cancer and a potential target for ovarian cancer therapy.